Rates of Variants of Uncertain Significance Among Patients With Breast Cancer Undergoing Genetic Testing: Regional Perspectives - Abdel-Razeq, Hikmat; Tamimi, Faris; Abujamous, Lama; Abdel-Razeq, Rashid; Abunasser, Mahmoud; Edaily, Sara; Abdulelah, Hazem; Khashabeh, Razan Abu; Bater, Rayan (Frontiers in Oncology, 2022)
Purpose: Contrary to BRCA pathogenic variants, recommendations for management of Variants of Uncertain Significance (VUS) are not clear and focus more on patient’s family and personal history of cancer. Local and regional data on VUS is scarce. In this paper we study patterns and frequency of VUS among breast cancer patients undergoing genetic testing. Patients and Methods: Patients with breast cancer at high risk for pathogenic variants, as per the National Comprehensive Cancer Network (NCCN) guidelines, were tested at reference laboratories. Related surgical interventions were reviewed. Results: Among a group of 1197 patients with breast cancer who underwent genetic testing and counseling, 110 (9.2%) had VUS; most (n=79, 71.8%) were in BRCA2. Median age (range) was 39 (25-66) years with 65 (59.1%) patients were 40 years or younger at diagnosis. Among 103 patients with nonmetastatic disease, 48 (46.6%) had breast conserving surgery (BCS) while only 5 (4.9%) had bilateral mastectomies; all were due to bilateral disease and not prophylactic. VUS diagnosis was known prior to initial surgery in 34 (33.0%) patients; 11 (32.4%) of them had BCS only. Over the study period, only one VUS variant was upgraded to "likely positive". The recent introduction of multiple gene panel testing had resulted in a surge in VUS rate (22.2%) in genes other than BRCA1 or BRCA2, like PALB2, CHEK2 and ATM. Conclusions: Rates of VUS are relatively high and increasing, mostly in non-BRCA1 or BRCA2, and this had no impact on the therapeutic or prophylactic surgical decisions. Adherence to guidelines is extremely important to avoid unnecessary procedures.